Detecting Plasma Produced by Laser in a Micromachining System as In-process Control - Toro Salazar, Cinthya Emma (2011)
Automated systems have been used in industries with high-volume production because automation has led, for example, the possibility to reduce costs, increase productivity, and increase accuracy, among others. On the other hand, it is also known that the processing laser is ideal for all kind of controls. In this sense, the amount of material produced and removed by laser irradiation on the surface of the substrate might be used as a control variable. Therefore, plasma detector could be used as part of the control system in the machining process in gaseous environments. This work presents the results of the preliminary characterization of this detector designed to measure theplasma generated during laser machining in air (Pamb and Tamb).